Eksplorasi Ethnomatematika dan Nilai Pendidikan Karakter Pada Ornamen Masjid Gedhe Kauman - Khusnul, Eva; Arfinanti, Nurul (Delta: Jurnal Ilmiah Pendidikan Matematika, 2025)
Cultural mathematics is an approach to designing mathematics that is relevant and closely related to cultural communities. Learning that focuses on cultural aspects becomes more interesting and enjoyable due to socio-cultural constructions, where mathematics has been integrated in human history and activities. This approach to learning that combines math and culture is known as ethnomathematics. One of the cultural and historical places is the Gedhe Kauman Mosque in Yogyakarta. This research aims to explore mathematical concepts based on the ornaments in the Kauman Gedhe Mosque and the value of character education for students. This research is qualitative research using ethnographic approach. Data were collected through interviews, field notes, observations, literature review, and documentation. Based on the results of the study, it was found that the concepts of mathematics in the Gedhe Kauman Mosque building in the form of flat geometry, geometric transformation, and character education values. This can be found in the ornaments of the gate, gate, front door of the mosque, side foundation of the foyer building, foundation of the main building, fort, main pillar of the foyer building, and the main door. Then character values include selflessness, hard work, responsibility, fortitude and wisdom, leader, and confidence.